Estudo espectroscópico da molécula RbCs: um novo paradigma para as curvas de potencial - Nogueira, Andreia de Faria (2008)
This study analyzes the spectrum of some electronic states of the RbCs molecule, where the spectra were obtained at the the Laboratoire Aimée Cotton, Orsay, France, whose transitions were excited from the electronic ground state X1 Σ + to the state 41 Σ + and the state A1 Σ + through tunable single mode dye lasers. We present in this work the potential energy curves of electronic states 41 Σ +, A1 Σ + and b3 Π of the molecule of RbCs. The potential energy curves will be described based on spectroscopic analysis of the molecule and for the electronic states A1 Σ + and b3 Π the DVR method and the Hannover potential will be used, since the RKR method is not the most appropriate model for strongly perturbed states. For the electronic state 41 Σ+, besides the method DVR and the Hannover potential, the Dunham model and the RKR potential will be used in order to compare the results between them. Even regarding the potential of the electronic state 41 Σ +, the results obtained in this work satisfactorily meet the latest theoretical results.